x+83+x+63+40=180

Simple and best practice solution for x+83+x+63+40=180 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for x+83+x+63+40=180 equation:


Simplifying
x + 83 + x + 63 + 40 = 180

Reorder the terms:
83 + 63 + 40 + x + x = 180

Combine like terms: 83 + 63 = 146
146 + 40 + x + x = 180

Combine like terms: 146 + 40 = 186
186 + x + x = 180

Combine like terms: x + x = 2x
186 + 2x = 180

Solving
186 + 2x = 180

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-186' to each side of the equation.
186 + -186 + 2x = 180 + -186

Combine like terms: 186 + -186 = 0
0 + 2x = 180 + -186
2x = 180 + -186

Combine like terms: 180 + -186 = -6
2x = -6

Divide each side by '2'.
x = -3

Simplifying
x = -3

See similar equations:

| 5(n-7)=-35+5n | | 0=-4t^2+t+9 | | -7(2T+6)=-14 | | 0.4x-14=20 | | 6x+y=zforx | | 4(F-7)=24 | | 2xy-7y=5 | | -8(S+4)=-12 | | 13s-3=10 | | x+54+x+82+56=180 | | -4(n+7)+1=-4n-23 | | 150=4(6*5)+2(6h) | | bx+a=ab | | 7x+14=3x+34 | | 2x-7=-6X+17 | | 4(4S+2)=136 | | (6+y)-Y=6 | | .5x+1=-.67+15 | | 6x^2+24x=42 | | 3y-3-5y=3-2y | | 4n-5=6 | | -7m-4m=22 | | 150=4(6*4)+2(6h) | | l+8=26 | | f*-2=2*-2+5 | | sin(x)=1.22 | | w-8=106 | | 5x+3=5x-10+77 | | -3(5+7x)=-40+4x | | 12+6m=7m-6(m-2) | | r+4=15 | | 0=2.4x^2+4.2x+1.2 |

Equations solver categories